A Novel Monitoring Dashboard And Hardware Implementation Simplifying The Remote Access In Industry - KORKMAZ, HAYRİYE (My University, 2023)
In today\"s world where technology is developing with a great speed, it is getting harder day by day to adapt or include changes on new technology to the processes in facilities. Insisting on using conventional solutions adopted so far in industrial facilities cause problems to compensate the changing fast consumption needs of today. Adopting recent technologies improves the maintenance and troubleshooting processes of the facilities, accelerates the production and increases the quality of production. In this way, technology based smart systems can provide the devices or machines with the skills required for problem solving and system development in the industry. In this study, a remote monitoring and control application is proposed for a frequency inverter which is widely used and critical device for motor driving in industrial facilities is discussed and a novel internet of things (IoT) based communication gateway is developed. In this way, it is intended to improve the problem solving skills of field personnel by contributing with remote support.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; ALETLER & GÖSTERİM; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, MANUFACTURING; Yapay Zeka; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Endüstri ve İmalat Mühendisliği; Kontrol ve Optimizasyon; Enstrümantasyon; Artificial Intelligence; Physical Sciences; Computer Networks and Communications; Industrial and Manufacturing Engineering; Control and Optimization; Instrumentation; Frequency Inverters; Industrial IoT; Machine-Cloud-Human Interaction; Remote Monitoring and Control; Smart Factories; Smart Machines